2018
DOI: 10.1016/j.jhep.2018.05.028
|View full text |Cite
|
Sign up to set email alerts
|

hiPSC hepatocyte model demonstrates the role of unfolded protein response and inflammatory networks in α1-antitrypsin deficiency

Abstract: This study compared the gene expression and protein profiles of healthy liver cells and those affected by the inherited disease α-antitrypsin deficiency. This approach identified specific factors primarily present in diseased samples which could provide new targets for drug development. This study also demonstrates the interest of using hepatic cells generated from human-induced pluripotent stem cells to model liver disease in vitro for uncovering new mechanisms with clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 50 publications
4
47
0
Order By: Relevance
“…This suggested that in live cells, inclusions are physically separated from one another. More recently, similar results were replicated in hepatocytes derived from human induced pluripotent stem cells, which spontaneously develop similar fragmentation of the ER when Z‐α 1 ‐antitrypsin is expressed under the control of its endogenous promoter [Segeritz et al., ]. When we performed three‐dimensional electron micrography on cells heterologously expressing Z‐α 1 ‐antitrypsin, we saw no evidence of tubular connections between inclusions even at a resolution of 18 nm (Figure D).…”
Section: Protein Mobility – Fragmented Ersupporting
confidence: 74%
“…This suggested that in live cells, inclusions are physically separated from one another. More recently, similar results were replicated in hepatocytes derived from human induced pluripotent stem cells, which spontaneously develop similar fragmentation of the ER when Z‐α 1 ‐antitrypsin is expressed under the control of its endogenous promoter [Segeritz et al., ]. When we performed three‐dimensional electron micrography on cells heterologously expressing Z‐α 1 ‐antitrypsin, we saw no evidence of tubular connections between inclusions even at a resolution of 18 nm (Figure D).…”
Section: Protein Mobility – Fragmented Ersupporting
confidence: 74%
“…Directed differentiation protocols for the derivation of hepatic cells from iPSCs and their application to model liver disease are well established ( Rashid et al., 2010 , Segeritz et al., 2018 , Smith et al., 2015 , Wilson et al., 2015 ). A significant hurdle in these protocols, however, has been the ability to compare the relative efficiency of differentiation across experiments as liver-specific lineage markers, such as AFP , are expressed in early hepatoblasts while more mature hepatocyte genes, such as ASGR1 , mark only a minority of cells in current differentiation protocols ( Warren et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patient-derived induced pluripotent stem cells (iPSCs) have emerged in recent years as a model system capable of reproducing human disease phenotypes, including AATD ( Rashid et al., 2010 , Segeritz et al., 2018 , Tafaleng et al., 2015 , Wilson et al., 2015 ). Through the application of directed differentiation protocols, these pluripotent cells can be utilized to study disease mechanisms in a variety of differentiated cell types, including those representing the two organs most affected in AATD, lung and liver ( Jacob et al., 2017 , McCauley et al., 2017 , Rashid et al., 2010 , Segeritz et al., 2018 , Tafaleng et al., 2015 , Wilson et al., 2015 ). Patient iPSCs likewise allow the generation of multiple cell types from a single genetic background, a significant advantage in modeling multiorgan diseases ( Leung et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…AKR1B10 and AKR1B1 are closely related to inflammation [ 15 , 19 ], and AKR1B10 in particular regulates inflammatory factors in the tumor microenvironment, which mobilizes the host immune response and promotes tumor suppression [ 15 , 19 , 49 ]. FGF1 activation is mediated via the PI3K-Akt signaling pathway that lies upstream of mTOR [ 50 ], which is related to autophagy, apoptosis and metabolism of cancer cells, as well as the NLRP3-mediated inflammatory response [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%